2020
DOI: 10.1186/s12885-020-07058-y
|View full text |Cite
|
Sign up to set email alerts
|

Immune landscape of human prostate cancer: immune evasion mechanisms and biomarkers for personalized immunotherapy

Abstract: Background Despite recent advances in cancer immunotherapy, the efficacy of these therapies for the treatment of human prostate cancer patients is low due to the complex immune evasion mechanisms (IEMs) of prostate cancer and the lack of predictive biomarkers for patient responses. Methods To understand the IEMs in prostate cancer and apply such understanding to the design of personalized immunotherapies, we analyzed the RNA-seq data for prostate adenocarcinoma from The Cancer Genome Atlas (TCGA) using a comb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 37 publications
(26 citation statements)
references
References 38 publications
1
17
0
Order By: Relevance
“…Remarkably, despite the loss of PTEN being associated with higher expression of the immune checkpoint gene programmed death ligand-1 ( PD-L1 ) in several cancer types [ 76 , 77 ], this is not true in PCa [ 78 ]. It has been shown that PCa employ different combinations of immune evasion mechanisms such as immunological ignorance, upregulated cytotoxic T lymphocyte-associated protein 4, and upregulated decoy receptor 3 [ 79 ]. So far, current immunotherapeutic interventions, such as PD-1 blockade, in PCa have not been successful.…”
Section: Discussionmentioning
confidence: 99%
“…Remarkably, despite the loss of PTEN being associated with higher expression of the immune checkpoint gene programmed death ligand-1 ( PD-L1 ) in several cancer types [ 76 , 77 ], this is not true in PCa [ 78 ]. It has been shown that PCa employ different combinations of immune evasion mechanisms such as immunological ignorance, upregulated cytotoxic T lymphocyte-associated protein 4, and upregulated decoy receptor 3 [ 79 ]. So far, current immunotherapeutic interventions, such as PD-1 blockade, in PCa have not been successful.…”
Section: Discussionmentioning
confidence: 99%
“…We studied the rearrangements of the immune system at one and three months in order to avoid early stimulus of postoperative stress (stress hormone ejection, WBC, and cytokine fluctuations). The high immunogenicity of PCa [19] offers a unique platform to study tumor excision effects on sparing or even boosting postoperative immunosurveillance function. However, the specific markers indicating immune rearrangement in progressing PCa or following RP are yet to be elucidated [20].…”
Section: Discussionmentioning
confidence: 99%
“…Bou-Dargham et al identified eight different immune evasion clusters, in which the majority of the clustered PCa patients (around 90%) exhibited immunological ignorance that can result from the absence of tumor-specific antigens that activate the immune system, or from the failure of antigen-presenting cells to recognize cancer antigens. Interestingly, they also reported a series of biomarkers that could predict responses to various immunotherapies CD48, SP140, KIRREL, RHOB, FBXO17, ANAPC1, EGFR, SOCS3, ALOX15, and UBR2 [ 43 ].…”
Section: Molecular Markers Predicting Significant Disease or Response To Therapymentioning
confidence: 99%